The art of film projection : a beginner's guide - Cherchi Usai, Paolo; Christiano, Spencer; Dean, Tacita, 1965-; Nolan, Christopher, 1970-; Surowiec, Catherine A.; Wagner, Timothy J. (George Eastman Museum, 2019)
The Art of Film Projection: A Beginner's Guide' is a beautifully produced, comprehensive outline of the materials, equipment and knowledge needed to present the magic of cinema to an enthralled audience. Part manual and part manifesto, The Art of Film Projection compiles more than 50 years of expertise from the staff of the world-renowned George Eastman Museum and the students of the L. Jeffrey Selznick School of Film Preservation into the most complete and accessible guide to film projection ever produced. The product of more than ten years of painstaking work by renowned film preservation specialists, and featuring a foreword by Tacita Dean and Christopher Nolan, this volume addresses a changing film landscape. No film comes to life until it is shown on the big screen, but with the proliferation of digital movie theaters, the expertise of film projection has become increasingly rare. Written for both the casual enthusiast and the professional projectionist in training, this book demystifies the process of film projection and offers an in-depth understanding of the aesthetic, technical and historical features of motion pictures. Fully accessible to the layperson, student, technician or scholar, the book is designed to be used: richly illustrated with photographs and easy-to-read diagrams, it is printed at a size that is easy to carry, with a ribbon bookmark and pages for notes. The Art of Film Projection invites readers to help save the authentic experience of seeing motion pictures on film.